Improving Anaerobic Digestion of Wheat Straw by Plasma-Assisted Pretreatment. (5th June 2013) - Heiske, Stefan; Schultz-Jensen, Nadja; Leipold, Frank; Schmidt, Jens Ejbye
Abstract : Plasma-assisted pretreatment (PAP) of lignocellulosic biomass has been shown to be an efficient method to decompose lignin and consequently facilitate microbial access to cellulose and hemicellulose. In the present study, PAP was tested for its suitability to enhance bioconversion of wheat straw to methane. In thermophilic batch experiments, methane yields of up to 366 mL/g volatile solids (VSs) were achieved, accounting for a yield increase of 45%. Common lignin-derived inhibitors like 5-hydroxymethylfurfural (5-HMF) and furfural were not detected after PAP, but toxicity test resulted in lower methane yields at higher substrate concentrations, indicating the presence of other unidentified inhibitors. However, in a continuous lab-scale biogas reactor experiment, stable codigestion of cattle manure with 20% PAP wheat straw was demonstrated, while no signs of adverse effects on the anaerobic digestion process were observed. After the introduction of the pretreated wheat straw to the reactor, volatile fatty acid concentrations remained low and stable, while gas production increased. In co-digestion, the PAP wheat straw was converted at an average yield of 343 mL CH4 /gVS.